Mixing qualitative and quantitative methods in formulating KMSS within the context of malaysian PIHE - Abdul Rahman, Azizah; Alias, Rose Alinda; Md. Saad, Nor Hasliza (2012)
The purpose of this article is to demonstrate how quantitative and qualitative methods collaborate and apply in formulating KMS strategy within the context of Malaysian PIHE. The latter is used to explore and identify special interest case study sites, while the former will be done to understand the process and context of real situation. Throughout the analysis the multiple perspectives theory by Mitroff and Linstone (1993) will be employed to represent the essential perspectives that need to take into consideration in formulating KMS strategy. This study emphasised on the holistic way of formulating KMS strategy by combining both technical and non-technical issues involving in an organization. This article elucidates the process of (a) how do both quantitative and qualitative methods involve? (b) how do the data is going to be analyze? And (c) what are the expected output of the methods?. The processes reflect upon the objective to answer the two main research questions; (a) How to formulate a more holistic strategy using multiple perspectives theory for KMS implementation in Malaysia PIHE context ? and (b) What factors conspire to influence the formulation of KMS strategy?